Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm trying show that if $p,q$ are Holder Conjugates then: $$\forall\, a\in\mathbb{R}^{n}:\,\Vert a\Vert_{q}=\max_{x\in\mathbb{R}^{n},\,\Vert x\Vert_{p}=1}\left<a,x\right>$$ Where $\left<a,x\right>$ is the Euclidian Inner-Product on $\mathbb{R}^{n}$ .

Immediately from Holder's Inequality I get that: $$\max_{x\in\mathbb{R}^{n},\,\Vert x\Vert_{p}=1}\left<a,x\right>\le\Vert a\Vert_{q}$$ To show the other direction of the inequality I wanted to pick a $v\in\mathbb{R}^{n}$ such that $\Vert v\Vert_{p}=1$ and $\left<a,v\right>=\Vert a\Vert_{p}$ but I can't seem to manage to do that. Since it's also easy to show that: $$\max_{x\in\mathbb{R}^{n},\,\Vert x\Vert_{p}=1}\left<a,x\right>=\max_{x\in\mathbb{R}^{n},\,\Vert x\Vert_{p}\leq1}\left<a,x\right>$$ It would also suffice to find a $v$ with $\Vert v\Vert_{p}\leq1$.

Help would be appreciated!

share|cite|improve this question
Look at how Hölder's inequality is usually proved, ie, Young's inequality. This gives a condition for equality, namely there are constants $\alpha>0, \beta>0$ such that $\alpha|a_k|^q = \beta|x_k|^p$ for all $k$. You could simplify life by assuming $\|a\|_q= 1$ to start with. – copper.hat Dec 28 '12 at 20:01
Try $x_k = \text{sgn } a_k |a_k|^{\frac{q}{p}}$. – copper.hat Dec 28 '12 at 20:15
That choice of vector doesn't seem to yield the right result unless I'm making some error in calculation, did you check it out? – Serpahimz Dec 28 '12 at 21:10
I added an answer below. – copper.hat Dec 28 '12 at 23:50
up vote 1 down vote accepted

Let $x_k = \text{sgn } a_k |a_k|^{\frac{q}{p}}$. Then $x_k a_k = (\text{sgn } a_k) a_k |a_k|^{\frac{q}{p}} = |a_k|^{\frac{q}{p}+1} = |a_k|^q$, and $\sum x_k a_k = \|a\|_q^q$. In addition, we have $\sum_k |x_k|^p = \sum_k |a_k|^q = \|a\|_q^q$, and so $\|x\|_p = \|a\|_q^{\frac{q}{p}}$.

Hence we have $\sum_k x_k a_k =\|a\|_q^{\frac{q}{p}} \|a\|_q^{q-\frac{q}{p}} = \|x\|_p \|a\|_q$. Then choosing $v = \frac{1}{\|x\|_p} x$ will produce the desired result.

share|cite|improve this answer
Indeed, I made a calculation error before but I've sorted it out since and reached the same result. I also took your previous advice and simplified it by assuming $∥a∥q$=1. Thanks for the help! – Serpahimz Dec 29 '12 at 0:04
You are very welcome! – copper.hat Dec 29 '12 at 0:10

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.